Coolbox Design for Traditional Fishing Vessel Using Sengon Wood (Paraserianthes falcataria (L.) Nielsen) Sawdust and Rice Straw Insulation - Baheramsyah, Alam; Wardhana, Ede Mehta; Sihombing, Puteri Ladikha (International Journal of Marine Engineering Innovation and Research, 2025)
Increased production of Indonesia catch fish accompanied by increased coolbox using to maintain freshness of fish. The efforts to maintain freshness of fish during this time is use a coolbox made from styrofoam which is not environmental friendly. Therefore, it is need to make cool box with environment friendly material and also effective for fish preservation . In this research, coolbox is modified with insulation based on Sengon wood sawdust (Paraserianthes falcataria (L.) Nielsen) and rice straw. Using the sawdust of sengon wood and dried straw pieces , experiments conducted to get the best composition of insulation, insulation variated with 2 different adhesives, PVAc and polyurethane .The results of the density test and thermal conductivity test, also in terms of preparation of various insulation variations, show that insulation with 66% sawdust of sengon wood; 28% straw; and 6% polyurethane adhesive is the best insulation to be used in coolbox, with thermal conductivity of 0.54 W / mK and density of 0.38 gr / cm3. The experiment in coolbox is done for 24 hours with 48 times data retrieval. Used ice cubes with a mass of 2.0 kilograms and 400 grams tuna fish. The experimental results show the minimum temperature that can be achieved coolbox is -0.1 ° C below the surface of ice .In fish body, the lowest temperature that can be achieved is 3, 2 ° C. While in the coolbox room, the lowest temperature is 19.4 ° C. The results also show coolbox with sengon sawdust and rice straw insulation able to preserving fish for 15 hours, with weight ratio between fish and ice is 1: 5.